Employee Performance on the MSME Business Before and After the Covid-19 Pandemic - Iman Setiyawan; Yugi Primacipta; Dwi Epty Hidayaty; Santi Pertiwi Hari Sandi (Formosa Journal of Applied Sciences, 2023)
The purpose of this observation is to find out the performance of employees before and after the impact of the corona virus pandemic on MSMEs in Indonesia, especially the culinary business of the Seblak Seafood Ateu MSME. This observation uses a descriptive approach method with observative. The results of this observation reveal that there has been a very significant change in employee performance due to COVID-19 since its appearance at the end of 2019. When the effects of the COVID 19 pandemic occurred in the Seblak Seafood Ateu business actor, turnover fell due to the limited PPKM. Employee performance before Covid 19, which was originally running normally, experienced a change in the performance of the employees, which decreased due to illness at the start of the Covid 19 outbreak, so employee productivity also decreased.